Multimorbidity from Chronic Conditions among Adults in Urban Slums: The AWI-Gen Nairobi Site Study Findings - Shukri F. Mohamed; Tilahun Nigatu Haregu; Olalekan A. Uthman; Christopher Khayeka-Wandabwa; Stella Kagwiria Muthuri; Gershim Asiki; Catherine Kyobutungi; Paramjit Gill (Ubiquity Press, 2021)
Background:In the era of double burden of infectious and non-communicable diseases in sub-Saharan Africa, the burden of multimorbidity is likely to be common. However, there is limited evidence on the burden and its associated factors in the sub-Saharan African context. Objective:The aim of this study was to determine the levels and identify determinants of multimorbidity from chronic conditions in two urban slums in Nairobi. Methods:Data collected from 2003 study participants aged 40-60 years in two urban slums of the Nairobi Urban Health and Demographic Surveillance System in 2015 were used. Using self-report, anthropometry and key biomarkers, data on 16 conditions including chronic diseases, behavioral disorders and metabolic abnormalities were gathered. Lifetime multimorbidity defined by the occurrence of at least two chronic conditions in an individual at any time during their life course was computed. Factors associated with lifetime multimorbidity were identified using multiple logistic regression. Findings:A total of 2,081 chronic conditions were identified among 1,302 individuals. While 701 (35.0%) had no chronic condition, single morbidity was reported in 726 (36.2%) of the study population. The overall prevalence of lifetime multimorbidity was 28.7%. The prevalence of dyads and triads of simultaneous occurrences of conditions (episodic multimorbidity) was 20.8% and 6.1%, respectively. Single morbidity was positively associated with gender and alcohol consumption; and negatively associated with employment. Women, older people, the unemployed, current smokers and current alcohol consumers had higher levels of lifetime multimorbidity in the study population. Interpretation:The findings of this study indicate that a considerable proportion of adults living in urban slums experience multimorbidity from chronic conditions. Further studies with a better rigor to establish temporal associations between socio-demographic factors and the occurrence of chronic conditions are needed to explore the impacts and implications on health status and health system.